Peran Penyuluhan Dalam Pemberdayaan Petani Kelapa Sawit Pola Swadaya di Kabupaten Kampar - Karim Sirait; Rosnita '; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this research are : (1) To identify the role of extension on oil palm independent smallholder farmers; (2) To know empowerments level of the farmers (3) To analyse the relation between extension’s role and  empowerment of  the farmers in Kampar District. This research was conducted at Sikijang Village at Tapung Hilir sub-district and Bukit Kemuning village at Tapung Hulu sub-district. Research’s samples was determined by purposive sampling methods by consideration that the location has active extension activities and has farmers group. The sample number are 60 the farmers. Validity and reliability analysis has been done on the measuring instruments by conduction try out to 30 respondents. Data’s analysis to acknowledge the first and second research purpose used Scale Likert’s summated Rating (SLR), whereas multiple linear regression was used to acknowledge the third purpose of this research. The Result showed that: (1) Extension role has been instrumental in the farmers activities as seen from the education, dissemination, facilitation, consultation, supervision, monitoring and evaluation variables; (2) Extension activities has been going well in empowering human resources, productive economy, and the farmers institutional in Kampar Regency; and (3) Empowerment of the farmers affected significantly by the role of extension in education, facilitation and consultation, and monitoring and evaluation, while the role of extension does not significantly effecting on dissemination and supervision of the farmers empowerments.   Keywords: extension’s role, empowerments, independent smallholder farmers, palm oil